2021
DOI: 10.3892/ijo.2021.5220
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone, a novel PDK 4 inhibitor, suppresses bladder cancer cell invasiveness via the mTOR/β‑catenin/N‑cadherin axis

Abstract: The phosphorylation of pyruvate dehydrogenase (PDH) by pyruvate dehydrogenase kinase (PDK) 4 inhibits its ability to induce a glycolytic shift. PDK4 expression is upregulated in various types of human cancer. Because PDK4 regulation is critical for metabolic changes in cancer cells, it is an attractive target for cancer therapy given its ability to shift glucose metabolism. It was previously shown that a novel PDK4 inhibitor, cryptotanshinone (CPT), suppressed the three-dimensional (3D)-spheroid formation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…Furthermore, GO and KEGG enrichment analysis revealed that PDK1-3 was correlational with the critical biological process involved in tumorigenesis, including nucleotide excision repair, DNA replication, RNA splicing, etc., presenting PDK1-3 as potential therapeutic targets for BCa. However, the decreased expression levels of PDK4 in the mixed and glycolytic subtypes did not match our inferences and was inconsistent with other reports [ 56 , 57 ]. Further studies are needed to investigate the roles played by PDKs in BCa development.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GO and KEGG enrichment analysis revealed that PDK1-3 was correlational with the critical biological process involved in tumorigenesis, including nucleotide excision repair, DNA replication, RNA splicing, etc., presenting PDK1-3 as potential therapeutic targets for BCa. However, the decreased expression levels of PDK4 in the mixed and glycolytic subtypes did not match our inferences and was inconsistent with other reports [ 56 , 57 ]. Further studies are needed to investigate the roles played by PDKs in BCa development.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, inhibition of PDK has been recognized as an attractive strategy in anticancer therapy [ 54 , 55 ]. While the roles and mechanisms of PDK1-3 in BCa remain unknown, enhanced PDK4 expression in BCa has been reported in previous studies, and PDK4 inhibitors were found to suppress BCa cell invasiveness and to potentiate cisplatin-induced cell death [ 56 , 57 ]. In this study, we observed significantly lower PDK1-3 expression levels in the quiescent subtype as compared to the other subtypes, consistent with the notion that PDKs contribute to tumorigenesis by inhibiting PDC activity [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process is detrimental to cancer cells and suppresses 3D-spheroid formation in malignant pancreatic cancer cells containing mutant KRAS. Previously, we showed that CPT suppresses cancer cell invasiveness and metastasis in a mouse model ( 28 ). Thus, CPT is expected to be a potent therapeutic drug for KRAS-driven intractable cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate Dehydrogenase Kinase (PDK) generates four kinase families in humans. PDK4 is mainly expressed in muscle and affects glucose consumption during metabolism (53). It has been reported in the literature that when PDK4 was stably inhibited, colorectal cancer cell migration and invasion were reduced, and apoptosis was increased.…”
Section: Discussionmentioning
confidence: 99%